Kajian Biblika Tentang Amanat Agung Dan Implikasinya Terhadap Misi Kristen - Dolfie Lumimpah (Sekolah Tinggi Agama Kristen Lentera Bangsa Manado, 2022)
The church has a purpose stated in Matthew 28:19-20, the verse known as the Great Commission, this commandment is related to God's most important commandment, namely to make all nations elect. The process and implementation of God's Great Commission commandments in accordance with Matthew 28:19-20 Substantially and actualized in the context of a changing era and making information on the gospel message spread quickly through technology that continues to develop. The method used in this research is descriptive textual method (biblical) while the data collection used is library research or library research on several relevant literatures with the subject matter discussed. After conducting a literature review and several attempts through the author's contribution in the form of interpretations, assumptions and assumptions about the main points of the Great Commission, the author concludes that the Mission of Jesus is the global mission of the church today, whatever the concept, design, design or color of the church, the main thing is whether the church can defend and maintain these two goals properly even in various crises that hinder doctrine such as differences in the way of disciples and baptism that often occur in our Christianity. The implication for today's Christian missions is that the first is how to answer the great mandate in 3 mission dimensions such as Holistic, Multicultural and Contextual. The development of an intense system of evangelism and discipleship as a form of obedience to God's commands to produce followers of Jesus who grow spiritually.